Assessment of Aflatoxin Contamination in Maize and Groundnuts during Storage in Giwa Community, Kaduna State Nigeria - Abdurrazaq, M.; Tijjani, M.B; Atta, H.I. (UMYU Journal of Microbiology Research)
Contamination of food and feed by aflatoxins has become a worldwide cause of public health concern due to its significant impact on human health and crop market value. The present study aimed to assess the aflatoxin contents of maize and groundnut from stores and warehouses in the Giwa community, Kaduna State, Nigeria. A total of ninety (90) grain samples of maize and groundnut were collected between October to December 2020 and analyzed for total aflatoxins using Enzyme-Linked Immuno Sorbent Assay (ELISA). Eighty-four 84(93.3%) of the samples had detectable aflatoxin levels (0.2-9.8ppb), while six 6(6.7%) had none. There was no significant difference (P>0.05) in the mean total aflatoxin content of the grains from stores, warehouses and household foodstuff samples. This could be attributed to agricultural practices and low temperature and humidity storage conditions, which were the same for all the stored grains. Overall, aflatoxin concentrations of the grain samples were within the acceptable limit (10ppb for maize and 15ppb for groundnut) for food safety set by NAFDAC. However, there could be further contamination during storage, particularly when temperature rises and humidity increases. Hence, improved storage conditions and monitoring of grain before sale are recommended to avoid contamination during storage and to ensure a healthy and safe food supply along the trade chain and to the consumers.